Phase I trial of 18F-Fludeoxyglucose based radiation dose painting with concomitant cisplatin in head and neck cancer. Issue 1 (July 2016) - Rasmussen, Jacob H.; Håkansson, Katrin; Vogelius, Ivan R.; Aznar, Marianne C.; Fischer, Barbara M.; Friborg, Jeppe; Loft, Annika; Kristensen, Claus A.; Bentzen, Søren M.; Specht, Lena
Abstract: Purpose: The CONTRAST (CONventional vs.Tumor Recurrence Adapted Specification of Target dose) phase I trial tested the safety of FDG PET guided dose redistribution in patients receiving accelerated chemo-radiotherapy for locally advanced head and neck squamous cell carcinoma (HNSCC). Methods and materials: CONTRAST was designed with two pre-defined dose-escalation steps to the FDG PET-avid volume (GTVPET ). The primary end point was any early grade 4+ toxicity according to Common Terminology Criteria for Adverse Events version 4.0 (CTCAE). The dose to GTVPET was escalated to a uniform prescription of 82 Gy EQD2 in the first step. All patients received accelerated radiotherapy (6 fractions a week) delivering 34 fractions of 2.34 Gy to the GTVPET as well as concomitant weekly cisplatin. Inclusion criteria were (1) primary SCC of oral cavity, oro- or hypo-pharynx, or laynx, (2) candidates for concomitant chemo-radiotherapy and (3) p16 negative tumors or p16 positive tumors in patients with smoking history of >10 pack years. GTVPET was defined by a specialist in nuclear medicine and a radiologist, while the anatomic GTV was defined in collaboration between an oncologist and a radiologist. Results: Median follow up time from the end of treatment was 18 months (range 7–21 months). All 15 patients completed treatment without interruptions and no incidents of early grade 4+ toxicity were observed. Four patients had ulceration at the evaluation two months after treatment, two have subsequently healed, but two remain, raising concerns regarding late effects. Conclusions: With all 15 cases having completed four month follow up and no incidence of early grade 4+ toxicity FDG PET based dose escalation to 82 Gy passed the protocol-defined criterion for dose escalation. However, two cases of concern regarding late outcome led us to refrain from further dose escalation and proceed with the current dose level in a larger comparative effectiveness trial.